(untitled) (The Review of Diabetic Studies, 2024)
Chronic and non-communicable diseases constitute an escalating public health challenge in Saudi Arabia, placing unprecedented demands on emergency medical services and contributing to preventable morbidity and mortality. This integrative review examines the current state of prehospital–primary care continuity for chronic disease emergencies within the Saudi healthcare context, with particular emphasis on emergency medical services and nursing integration strategies. A systematic search of PubMed, Scopus, and Web of Science databases identified 847 potentially relevant articles, of which 43 met inclusion criteria for detailed analysis. Findings reveal substantial fragmentation in care transitions between prehospital emergency responses and primary care follow-up, resulting in high rates of emergency department revisits and ambulance re-utilization among patients with diabetes, cardiovascular disease, and chronic respiratory conditions. Effective integration models identified internationally emphasize structured communication protocols, shared electronic health records, community paramedicine initiatives, and nurse-led chronic disease management programs. Implementation barriers specific to Saudi Arabia include geographic disparities in primary care access, incomplete health information exchange infrastructure, and limited paramedic scope of practice regarding chronic disease assessment. Evidence supports development of standardized handover procedures, risk stratification tools applied in prehospital settings, and systematic post-emergency primary care referral pathways as mechanisms to reduce avoidable emergency service utilization and improve long-term health outcomes for patients with chronic conditions.